MENINGKATKAN TEKNIK RENANG GAYA BEBAS MELALUI BANTUAN PELAMPUNG DAN FINS SWIMMING - Arief Sulaiman; Harda Dedali; Tatang Suryadin (JOURNAL RESPECS, 2021)
ABSTRACT. The problem in this study is that students in class 10 of IPS SMA 2 Majalengka have an average swimming technique that is not perfect, and the pedaling is not powerful. For this reason, tools are needed to improve his swimming technique as well as develop his physical condition. The author tries to use buoys and fins swimming in his swimming lessons. The research method used in this research is action research. In class 10 there are 12 people. The instrument used was a freestyle swimming assessment rubric. Result report, it is obtained an overview in cycle I of 4 students (33.3%) and 8 people (66.7%) who did not complete, in cycle II as many as 7 people (58.3%). complete students and 5 students (41.7%) did not complete, and in cycle III 11 people (91.6%) students completed learning freestyle swimming and 1 0rang (8.4%) did not complete. The learning outcomes of swimming which are the ultimate goal of swimming learning require maximum effort and improvement at each stage of learning. In addition, a very important factor in achieving these goals is a means of learning. Adequate equipment and good learning stages will have the opportunity to achieve learning objectivesKeywords: Learning Stages; Facilities; Learning OutcomesABSTRAK. Permasalahan dalam penelitian ini adalah peserta didik di kelas 10 IPS SMA 2 Majalengka rata-rata teknik renang tidak sempurna, serta kayuhan tangan kurang bertenaga. Untuk itu diperlukan alat bantu untuk memperbaiki teknik berenangnya sekaligus mengembangkan kondisi fisiknya. Penulis mencoba menggunakan pelampung dan fins swimming dalam pembelajaran renangnya. Metode penelitian yang digunakan dalam penelitian ini adalah Penelitian Tindakan.  Di kelas 10 jumlah orang sebanyak 12 orang. Instrumen yang digunakan adalah Rubrik penilaian renang gaya bebas. Hasil penelitian melaporkan diperoleh gambaran pada siklus I peserta didik yang tuntas dalam belajar sebanyak 4 orang (33,3%), dan 8 Orang (66,7 %) tidak tuntas, pada siklus II sebanyak 7 orang (58,3 %) peserta didik tuntas dan 5 orang (41,7 %) tidak tuntas, dan pada siklus III 11 orang (91,6 %) peserta didik tuntas dalam pembelajaran renang gaya bebas dan 1 0rang (8,4 %) tidak tuntas. Hasil belajar renang yang menjadi tujuan akhir dari suatu pembelajaran renang memerlukan upaya yang maksimal dan perbaikan pada setiap tahapan belajarnya. Selain itu faktor yang sangat penting dalam pencapaian tujuan tersebut adalah sarana pembelajaran. Peralatan yang memadai dan tahapan pembelajaran baik akan berpeluang pencapaian tujuan pembelajaran.Kata Kunci: Tahapan Pembelajaran; Sarana; Hasil Belajar